The Effect of Prelabour Rupture of Membranes on Circulating Neonatal Nucleated Red Blood Cells - AL-bayati, Maha M.; AL-Moayd, Hala Abdul Qader; Shubber, Lamees Adnan (AL-Kindy College Medical Journal, 2012)
Background: Prelabour rupture of membranes is a problem that faces the obstetricians. It has many maternal and fetal sequale and its etiology and management still controversial. Objective: To test the absolute nucleated red blood cells counts at birth in infants who are born after prelabour rupture of membranes. Methods: A prospective study conducted in AL-Kadhymia Teaching Hospital. Hundred pregnant women were included in this study. Fifty pregnant women who had prelabour rupture of membranes considered as group (1), other fifty pregnant women with intact membranes considered as group (2) through a period of one year. Nucleated red blood cell counts of venous cord blood obtained within one hour of life from 50 infants who were born after prelabour rupture of membranes. The same procedure was applied for the control group. Results: The nucleated red blood cell counts and Haematocrit were significantly higher in infants who were born after prelabour rupture of membrane than in the control group (P value <0.001 and 0.03 respectively). Conclusion: Infants born after prelabour rupture of membrane have higher nucleated red blood cell counts at birth than the control group.